Problematika Pendidikan Agama Islam di Pondok Pesantren - Baidawi , Abdul Hafiz (Universitas Islam Negeri (UIN) Mataram, 2023)
This article discusses several challenges in the teaching of Islamic Religious Education (PAI) at Pondok Pesantren Al-Ishlahuddiny Kediri, covering both the aspects of educators and students. These challenges include the interaction between educators and students, the need for more effective teaching methods, as well as time constraints, and the density of materials. Additionally, issues related to the mastery of content, administration, and learning facilities are also the focal points of discussion. Several solutions are proposed to address these issues, including improvements in the design of teaching tools, the enhancement of technology-based learning facilities, and better classroom management. The improvement of educators' quality through training and scholarly meetings, along with support for the development of appropriate teaching strategies and methods, is also considered crucial. In conclusion, this article summarizes the challenges and solutions in teaching Islamic Religious Education at Pondok Pesantren Al-Ishlahuddiny Kediri, to enhance the quality of Islamic education and shape students who are both qualified and virtuous. Keywords: Islamic Education, Islamic Boarding School, Education Problematics Artikel ini membahas sejumlah tantangan dalam pembelajaran (PAI) Pendidikan Agama Islam di Pondok Pesantren Al-Ishlahuddiny Kediri, mencakup aspek pendidik dan peserta didik. Tantangan ini meliputi interaksi antara pendidik dan peserta didik, kebutuhan akan metode pembelajaran yang lebih efektif, serta keterbatasan waktu dan padatnya materi. Disamping itu, permasalahan penguasaan materi, administrasi, dan sarana pembelajaran juga menjadi fokus pembahasan. Beberapa solusi diusulkan untuk mengatasi permasalahan ini, termasuk perbaikan dalam desain perangkat pembelajaran, peningkatan sarana pembelajaran berbasis teknologi, dan manajemen kelas yang lebih baik. Peningkatan kualitas pendidik melalui pelatihan dan pertemuan ilmiah, serta dukungan untuk pengembangan strategi dan metode pembelajaran yang sesuai, juga dianggap penting. Kesimpulannya, artikel ini merangkum tantangan dan solusi dalam pembelajaran PAI di Pondok Pesantren Al-Ishlahuddiny Kediri, dengan tujuan meningkatkan kualitas pendidikan agama Islam dan membentuk peserta didik yang berkualitas serta berakhlak mulia. Kata kunci: Pendidikan Islam, Prondok Pesantren, Problematika Pendidikan